Analysis of Differences in Daily Stock Returns and Stock Trading Volume After the Issuance of The Fatwa MUI No. 83 of 2023 Case Study of Israel Affiliated Companies in Indonesia - Arfiana Putri Ananda; Ani Silvia; Elmy Nur Azizah; Edi Setiawan (IECON: International Economics and Business Conference, 2025)
This study was conducted of analyzing the efficiency of the semi-strong market in response to the issuance of MUI Fatwa No. 83 of 2023 concerning Legal Protection for the Israeli-Palestinian Struggle. The fatwa calls on Indonesian Muslims to boycott products related to Israel. This study was conducted to see if there were any differences in daily stock returns (AR) and stock trading volume (TVA) for five companies that are thought to have ties to Israel and are listed on the Indonesia Stock Exchange, like PT Unilever Indonesia Tbk (UNVR), PT MAP Boga Adiperkasa Tbk (MAPB), PT Fast Food Indonesia Tbk (FAST), PT Sarimelati Kencana Tbk (PZZA), and PT Graha Prima Mentari (GRPM). This quantitative study uses an event study method with a 60-day event window (30 days before and after the issuance of the fatwa). Data were analyzed using the kolmogorov-smirnov test for normality and hypothesis testing with the non-parametric (wilcoxon signed rank test). Findings indicate no significant differences in AR (abnormal return) and TVA (trading volume activity) between periods before and after an event, suggesting the Indonesian capital market exhibits semi-strong efficiency. Thus, the fatwa announcement did not trigger an excessive market reaction.